In-Vitro Product Performance of Parenteral Drug Products: View of the USP Expert Panel - D'Arcy, Deirdre (My University, 2022)
Performance testing of parenteral products represents a broad arena of product types, test equipment, and analytical challenges. This Stimuli article is one in a series of Stimuli articles on product performance testing focused on common methodological approaches used and challenges encountered in the field of performance testing of injectable products. The article is complementary to In Vitro Release Test Methods for Parenteral Drug Preparations <1001> and takes into account the contents and acknowledges current trends in test apparatus and conditions, medium selection, and separation techniques. Limitations of current practices are presented, and recommendations highlight the need for biorelevant and predictive test environments, test standardization, and an understanding of the impact of the test conditions on the release kinetics and interpretation of test results
Keywords: Product performance testing; Injectables; Implantable drug products; Immunology, Inflammation & Infection; Nanoscience & Materials; DISSOLUTION TESTING